A positive psychology group intervention in Greek university students by the counseling center: Effectiveness of implementation - Kounenou, Kalliope; Kalamatianos, Antonios; Garipi, Aikaterini; Kourmousi, Ntina (Frontiers in Psychology, 2022)
Most institutions in higher education have emphasized success in knowledge while overlooking Students’ wellbeing. The present study aimed to examine the effectiveness of the implementation of a 5-week positive psychology group intervention to a sample of 69 students that were assigned to the intervention (N = 34) and the control group (N = 35). Pre and post measures were taken assessing positive and negative emotions, resilience, happiness, optimism, and self-esteem. In particular, Modified Differential Emotions Scale (mDES), Connor-Davidson Resilience Scale (CD-RISC), Subjective Happiness Scale (SHS), Life Orientation Test-Revised (LOT-R), and Rosenberg Self-Esteem Scale (RSES) were administered to the participants. A mixed measures design was employed with the condition experimental vs. control group as the between-participants factor and time, namely, baseline vs. post-intervention as the within-participants factor. Except for optimism, compared with students in the control group, students in the experimental group showed no significant differences at baseline and experienced a significant increase in positive emotions and resilience in the post-test. On the contrary, the control group demonstrated no significant difference at post-test. Additionally, the students of the intervention group reported significantly higher levels in all measures in comparison with the students of the control group, except resilience, at post-test. However, when the interaction of design and time was considered, the increase in positive emotions solely emerged as a significant result of the intervention. The implementation of a positive psychology group intervention program can be effective in helping students experiencing positive emotions. More research is needed in order to refine and improve the application of such a program in a university setting, in regard to long term intervention.